Screening of Phosphate-Solubilizing Fungi From Air and Soil in Yunnan, China: Four Novel Species in Aspergillus, Gongronella, Penicillium, and Talaromyces - Doilom, Mingkwan; Guo, Jian-Wei; Phookamsak, Rungtiwa; Mortimer, Peter E.; Karunarathna, Samantha C.; Dong, Wei; Liao, Chun-Fang; Yan, Kai; Pem, Dhandevi; Suwannarach, Nakarin; Promputtha, Itthayakorn; Lumyong, Saisamorn; et al. (Frontiers in Microbiology, 2020)
Phosphate-solubilizing fungi (PSF) play an important role in increasing the bioavailability of phosphorus in soils for plants. Thirteen fungal strains, one collected from air and 12 from soil, were screened and described here in detail. These fungal strains were tested for their ability to solubilize tricalcium phosphate (TCP) on both solid and liquid Pikovskaya (PVK) media in vitro. The airborne fungal strain KUMCC 18-0196 (Aspergillus hydei sp. nov.) showed the most significant phosphate solubilizing activity on a solid PVK medium with the solubilization index (SI) (2.58±0.04 cm) and the highest solubilized phosphates (1523.33±47.87 μg/mL) on a liquid PVK medium. To the best of our knowledge, Aspergillus hydei sp. nov. is the first phosphate-solubilizing fungus reported from air. We also provide the identification especially for Aspergillus, Penicillium and Talaromyces, generally reported as PSF. It is important to not only screen for PSF but also identify species properly so that researchers have a clearer taxonomic picture for identifying potential taxa for future plant growth-promoting applications. Herein, Aspergillus hydei (section Nigri), Gongronella hydei, Penicillium soli (section Lanata-Divaricata) and Talaromyces yunnanensis (section Talaromyces) are fully described and introduced as new to science. These four new species are identified based on both morphological characteristics and multigene phylogenetic analyses, including the genealogical concordance phylogenetic species recognition method where necessary. Penicillium austrosinense is considered to be a synonym of P. guaibinense.